Initial impact of SARS-Cov-2 vaccination on healthcare workers in Italy- Update on the 28th of March 2021 - Mateo-Urdiales, Alberto; Del Manso, Martina; Andrianou, Xanthi; Spuri, Matteo; D'Ancona, Fortunato P; Filia, Antonietta; Rota, Maria Cristina; Petrone, Daniele; Vescio, Maria Fenicia; Riccardo, Flavia; Bella, Antonino; Pezzotti, Patrizio; et al. (My University, 2021)
In Italy, the COVID-19 vaccination campaign started in December 2020 with the vaccination of healthcare workers (HCW). To analyse the real-life impact that vaccination is having on this population group, we measured the association between week of diagnosis and HCW status using log-binomial regression. By the week 22-28 March, we observed a 74% reduction (PPR 0.26; 95% CI 0.22-0.29) in the proportion of cases reported as HCW and 81% reduction in the proportion of symptomatic cases reported as HCW, compared with the week with the lowest proportion of cases among HCWs prior to the vaccination campaign (31 August-7 September). The reduction, both in relative and absolute terms, of COVID-19 cases in HCWs that started around 30 days after the start of the vaccination campaign suggest that COVID-19 vaccines are being effective in preventing infection in this group.
Keywords: COVID-19; Healthcare workers; Pandemic; Vaccines